PENGARUH KREDIBILITAS INFLUENCER, HARGA, DAN MEDIA SOSIAL TERHADAP MINTA BELI DI TOKOPEDIA (STUDI KASUS PADA MASYARAKAT KOTA MEDAN) - TRI MELDA MEI LIANA; DENNI ROSAULY PURBA (LP2MTBM MAKARIOZ, 2021)
This research aims to find out the influence of Influencer Credibility, Price, and Social Media on Buying Interest in Tokopedia(Case Study on Medan City Community). The sample used in the study was 100 respondents using questionnaires. Fromthe results of the multiple regression analysis test, namely: Y = 4.442 + 0.315 X1 + 0.468 X2 + 0.158 X3, shows that thePrice variable has a stronger influence compared to the Influencer Credibility variable and the Buy Interest variable. From thepartial test results, the Influencer Credibility variable is significant to the Buy Interest variable, the price variable is significantto the Buy Interest variable, and the Social Media variable is significant to the Buy Interest variable. Based on the results ofthe F test, influencer credibility variables, price variables, and social media variables together have a significant effect on theBuy interest variable. From the results of the R2 determination coefficient of influencer credibility variables, prices, and socialmedia can explain the variable of Buying Interest in Tokopedia by 97.1% while the remaining 2.9% is explained by variablesnot studied in the study.